Using cold plasma to investigate the mechanisms involved in cosmic dust formation: Role of the C/O ratio and metals. Issue Volume 15:Issue S350(2019) (April 2019) - Bérard, Rémi; Makasheva, Kremena; Sabbah, Hassan; Demyk, Karine; Joblin, Christine
Abstract: Using a cold plasma reactor in which we inject an organosilicon molecular precursor, we investigate chemical mechanisms that can be involved in dust formation in evolved stars. By injecting metal atoms into the gas-phase, we investigate the role of metals on dust composition. We show the formation of composite particles made of pure metal (silver) nanoparticles embedded in an organosilicon dust. We study the impact of oxygen and show that it can inhibit dust formation, likely through the destruction of nucleation seeds.